(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Objective: Sushruta has explained various methods for Vrana Chikitsa. Virechana is vital to remove the vitiated Dosha from the body in turn normalize them and prevent recurrence of the abscess. Vrana Pichu is one of the best substitutes for wound healing and Jathyadi Taila has better Shodhana and Ropana effect. Case: A case of 70 year old man, who presented with complains of swelling in left anterio-lateral aspect of the neck since 4 days along with fever, pain and discolouration of the skin has been taken for the study. Methods: Initial I&D was done followed by a course of antibiotics. Then Deepana and Pachana. After Abhyantara and Bahya Snehana and Svedana, Virechana was administered. Vrana Pichu, with Jatyadi Taila was done every day. Results: The result of the current case study is based on the size of the wound. Conclusion: The combination of Virechana and Vrana Pichu can be used as a line of treatment for the management.